Mapping Paratope and Epitope Residues of Antibody Pembrolizumab via Molecular Dynamics Simulation - Liu, Wenping; Liu, Guangjian (Bioinformatics Research and Applications, 2017)
Blocking the programmed death receptor 1 (PD-1)/programmed death ligand 1 protein (PD-L1) interaction has come up as a promising cancer immunotherapy. Pembrolizumab is a therapeutic monoclonal antibody targeting PD-1 and received widespread attention. However, the messages for the paratope and epitope residues of pembrolizumab are insufficient. Here molecular dynamics (MD) simulation was used to map epitope on PD-1 to paratope residues on pembrolizumab. A total of twenty-nine key residues were predicted in the PD-1/pembrolizumab interaction. Of the fourteen epitope residues, three (i.e., ASN66, LYS78 and ALA132 on PD-1) were found to play critical roles in the interaction of PD-1 and PD-L1. Therefore, pembrolizumab prevents PD-L1 from interacting with PD-1 through steric hindrance, and the key residues sorted out here were potential hotspots for the optimization of pembrolizumab.